2013
DOI: 10.1055/s-0033-1338842
|View full text |Cite
|
Sign up to set email alerts
|

SNAr-Derived Decomposition By-products Involving Pentafluorophenyl Triazolium Carbenes

Abstract: Pentafluorophenyl triazolium carbenes, widely used in NHC-catalysis, can decompose by several mechanisms. Under high concentration conditions, the azolium may undergo a pentafluorophenyl exchange by a proposed SNAr mechanism to give an inactive salt. In the presence of appropriate substrates, cyclization on the ortho-position of the arene can occur, also by SNAr. These adducts provide a potential pathway for catalyst decomposition and serve as a caveat to the development of new reactions and catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Although the formation of the NHC-bounded side reaction products might be sometimes observed during the investigations of various NHC organocatalytic transformations, to the best of our knowledge, there has been very limited reports on the characterization of those NHC-bounded reaction products ( Berkessel et al, 2013 ; Berden et al, 2021 ). A representative study was from Rovis and co-workers in 2013, when they reported a cascade cyclization reaction between the triazolium NHC catalyst bearing an N -pentafluorophenyl ( N -C 6 F 5 ) group and the isatin-derived α , β -unsaturated ester substrate ( Rovis et al, 2013 ) ( Figure 1B ). The spirocyclic product was characterized via X-ray analysis on the product crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Although the formation of the NHC-bounded side reaction products might be sometimes observed during the investigations of various NHC organocatalytic transformations, to the best of our knowledge, there has been very limited reports on the characterization of those NHC-bounded reaction products ( Berkessel et al, 2013 ; Berden et al, 2021 ). A representative study was from Rovis and co-workers in 2013, when they reported a cascade cyclization reaction between the triazolium NHC catalyst bearing an N -pentafluorophenyl ( N -C 6 F 5 ) group and the isatin-derived α , β -unsaturated ester substrate ( Rovis et al, 2013 ) ( Figure 1B ). The spirocyclic product was characterized via X-ray analysis on the product crystals.…”
Section: Introductionmentioning
confidence: 99%